The Spectra and the Duration of Low Vowels in Standard Lithuanian and Latvian - Kaukėnienė, Lidija (Respectus Philologicus, 2012)
This article analyses the quantity and quality features of the stressed and unstressed short and long low vowel phonemes [a] and [e] in Standard Lithuanian and Latvian, focussing on Lithuanian and Latvian trisyllabic words. This choice was dictated by the need to analyse the vowels in different positions, i.e., stressed, pre-accented, and post-accented. The spectra and duration of pre-accented and post-accented [a] and [e] were compared with those of the corresponding stressed vowels. The analysis is based on empirical research methods including the method of variational statistics. The article embraces synchronic, experimental, descriptive, and comparative approaches. The results of the investigation showed that the stressed and unstressed [a] and [e] differ in the Lithuanian and Latvian languages. Among stressed vowels, [e] demonstrates the greatest differences in acoustic and articulatory characteristics. The stressed Lithuanian [e] demonstrates greater diffusion (it is closer), higher timbre, and more advanced frontness than the Latvian equivalents. The Lithuanian [e·] is of lower timbre and more retracted back; [a] is of higher timbre and more front than the equivalent Latvian sounds. The [a] variants are more compact (open) than the Latvian vowels. The Lithuanian unstressed [e·], [e], [a·] are more diffuse (closer), of higher timbre, and show more retracted front than the equivalent Latvian vowels. Among unstressed vowels of the investigated languages, it is [a] that differs least in its acoustic and articulatory characteristics. The averages of the formants of Lithuanian unstressed vowels are closer to the frequencies of the neutral [ǝ]; less distinct qualitative characteristics of all long and short unstressed vowels were observed. The qualitative characteristics of Latvian unstressed vowels are more distinct. Their articulation is more precise and clearer. In both languages, the long stressed vowels [a] and [e] almost do not differ in their duration. The Lithuanian stressed long vowels are a little longer. In Standard Latvian, in nearly all positions, the long unstressed variants [a] and [e] are considerably longer than in Standard Lithuanian. The qualitative reduction of Lithuanian unstressed long vowels is significantly greater than it is in the Latvian language. That is why, in Lithuanian, the duration contrast between long stressed and long unstressed vowels is stronger than in Latvian. The duration of the short stressed and unstressed vowels [a] and [e] differs imperceptibly.